Laboratory monitoring of haemostasis. (January 2015) - Fowler, A.; Perry, D. J.
Summary: Peri‐operative coagulation monitoring should begin with the assessment of individual bleeding risk using a standardised bleeding history before the surgical procedure. Laboratory testing should be performed if this history is abnormal or peri‐operative bleeding is anticipated. This process sensitively identifies those at risk of peri‐operative bleeding and therefore minimises their peri‐operative risk, without costly and time‐consuming population testing. There are multiple potential causes of haemostatic derangement within the peri‐operative period, and an understanding of both normal haemostasis and the coagulation tests available to detect coagulopathy is required to optimise patient management. In bleeding patients, routine coagulation tests should be requested, but one should be aware of the major limitations that exist. Delay whilst waiting for these laboratory results, which, in turn, aggravates coagulopathy, bleeding, blood product requirements, length of surgery and overall morbidity and mortality.